2013
DOI: 10.1002/jgra.50153
|View full text |Cite
|
Sign up to set email alerts
|

The magnetospheric banana current

Abstract: [1] It is shown that the banana current, a current system in the inner magnetosphere closing entirely within the magnetosphere (i.e., not through the ionosphere or on the magnetopause) but not circumflowing around the Earth, is a regular feature of near-Earth space. Closure options for the eastward asymmetric current on the inside of a localized pressure peak were explored, with the conclusion that the current must close via westward current around the outside of the high pressure region. It is a current that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 67 publications
(78 reference statements)
1
68
0
Order By: Relevance
“…In addition, the difference of magnetic field B z is almost the same at t 0 -10 s and t 0 + 10 s, which strongly suggests that these three current form circuits, which are independent from the background magnetotail current. We point out that although the plasma pressure variation supports the picture of banana current loop, it may be not exactly the same as described in Liemohn et al (2013) since the DF is a kinetic structure that can not be fully interpreted by MHD theory. For the third current structure in Fig.…”
Section: The Re-distribution Of Cross-tail Current Densitymentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, the difference of magnetic field B z is almost the same at t 0 -10 s and t 0 + 10 s, which strongly suggests that these three current form circuits, which are independent from the background magnetotail current. We point out that although the plasma pressure variation supports the picture of banana current loop, it may be not exactly the same as described in Liemohn et al (2013) since the DF is a kinetic structure that can not be fully interpreted by MHD theory. For the third current structure in Fig.…”
Section: The Re-distribution Of Cross-tail Current Densitymentioning
confidence: 85%
“…However, the volume gradient of magnetic flux tube is extremely difficult to be accurately estimated in any magnetic field model in the perturbed magnetotail, especially accompanied with BBFs (Kubyshkina et al, 2011;Tsyganenko, 1995). Moreover, Liemohn et al (2013) suggested that current could flow in a closed loop around peaks in plasma pressure forming a banana current. This banana current is distinct from the other current systems in the near-Earth space.…”
Section: The Re-distribution Of Cross-tail Current Densitymentioning
confidence: 99%
“…Numerical experiments carried out by Liemohn et al . [, ] indicate that the small‐scale eastward current can reach L = 5–6 at times (e.g., Figure 4 in Liemohn et al . [, ]).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[, ] indicate that the small‐scale eastward current can reach L = 5–6 at times (e.g., Figure 4 in Liemohn et al . [, ]). Our multipoint analysis shows that the eastward component can indeed extend beyond r = 5 R E for weak storm times.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation